Drug repurposing for targeting cyclic nucleotide transporters in acute leukemias - A missed opportunity. (January 2021) - Perez, Dominique R.; Sklar, Larry A.; Chigaev, Alexandre; Matlawska-Wasowska, Ksenia
Abstract: While current treatment regimens for acute leukemia can dramatically improve patient survival, there remains room for improvement. Due to its roles in cell differentiation, cell survival, and apoptotic signaling, modulation of the cyclic AMP (cAMP) pathway has provided a meaningful target in hematological malignancies. Several studies have demonstrated that gene expression profiles associated with increased pro-survival cAMP activity or downregulation of various pro-apoptotic factors associated with the cAMP pathway are apparent in acute leukemia patients. Previous work to increase leukemia cell intracellular cAMP focused on the use of cAMP analogs, stimulating cAMP production via transmembrane-associated adenylyl cyclases, or decreasing cAMP degradation by inhibiting phosphodiesterase activity. However, targeting cyclic nucleotide efflux by ATP-binding cassette (ABC) transporters represents an unexplored approach for modulation of intracellular cyclic nucleotide levels. Preliminary studies have shown that inhibition of cAMP efflux can stimulate leukemia cell differentiation, cell growth arrest, and apoptosis, indicating that targeting cAMP efflux may show promise for future therapeutic development. Furthermore, inhibition of cyclic nucleotide transporter activity may also contribute multiple anticancer benefits by reducing extracellular pro-survival signaling in malignant cells. Hence, several opportunities for drug repurposing may exist for targeting cyclic nucleotide transporters.